Effect Of Career Development And Work Discipline On Employee Performance - Dhea Octafry Suggestion; Dewi Andriany (Proceeding International Seminar of Islamic Studies, 2019)
This study aims to determine and analyze the influence of career development and work discipline on employee performance both partially and simultaneously at PT. Pelindo 1 Belawan Domestic Container Terminal Branch. The type of research used is associative/relationship research. The population in this study was all non-shift employees at PT. Pelindo 1 Domestic Container Terminal Branch in the Finance and General Division, IT and Management Systems Division and Engineering Division which amounted to 54 people and the determination of the number of samples in this study was by making the population into a sample so that theampels of this study numbered 54. The source of this research data is primary data using research instruments in the form of questionnaires. The data collection method used is survey research. This study uses classical assumption tests, multiple linear regression analysis, hypothesis testing, and determination coefficient analysis for statistical analysis and regression models have been tested first in classical assumption tests. The results of the study stated that partial testing showed that career development had a significant positive effect on the performance of PT employees. Pelindo 1 Belawan Domestic Container Terminal Branch. Pengujian partially also shows that work discipline has a significant positive effect on the performance of PT employees. Pelindo 1 Belawan Domestic Container Terminal Branch and pengujian simultaneously showed that career development and work discipline have a significant effect on the performance of PT. Pelindo 1 Belawan Domestic Container Terminal Branch.